Timing of Atlantic salmon Salmo salar smolt migration predicts successful passage through a reservoir. Issue 5 (6th April 2018) - McLennan, D.; Rush, E.; McKelvey, S.; Metcalfe, N. B.
Abstract : Around 30% of Atlantic salmon Salmo salar smolts successfully survived passage through Loch Meig, a reservoir in the north of Scotland, en route to the sea. However, this survival rate was in turn dependent on the timing of migration, with the earliest migrants in the spring having the best chance of survival. This could have implication for fisheries management, since the estimation of smolt downstream survival may be influenced by which time period of the smolt run is analysed.